Phenomenology as a method to investigate the experience lived: a perspective from Husserl and Merleau Ponty's thought - Sadala, MLA; Adorno, RDF (Blackwell Publishing, 2002)
Aim. By taking nursing as a human relationships activity, in spite of its strong technical-scientific features, this article reflects on the phenomenological method as one of the ways to develop ail investigation and acquire knowledge of the topic.Rationale. Based on Husserl's phenomenology, which is opposed to the way of doing science based on the laws that regulate the physics and mathematics, the article introduces Merleau Ponty's existential phenomenology as the theoretical foundation for the method it proposes. My existential conceptions-people as historic beings inserted in a world over which they act but which, in its turn, determines them; the human perception as reference for our way of being in the world; the space-time structure of perception-these are the key concepts that have led to the elaboration of ail approach to phenomenological research.Proposal of a methodology. Steps are proposed for such ail approach, namely phenomenological description, reduction and analysis. These lead to the building up of ideographic and nomothetic analyses, thus unveiling and describing general truths about the phenomenon studied. Finally, the possibilities for applying the methodology to nursing research are discussed, illustrated by my research into student nurses' perspectives on working oil an isolation ward.
Keywords: phenomenology; nursing; research; Merleau Ponty; Husserl; qualitative research; existential phenomenology; phenomena; methodology; phenomenological method